Actitudes valóricas y habilidades sociales en el aula en estudiantes de la I.E.P.M. N° 61014 Horacio Zevallos Gámez, Iquitos 2023 - Vasquez Janeiro, Michael Jeffrey (2024)
The study presents important results that answer the following question: What is the relationship that exists between value attitudes and social skills in the classroom of I.E.P.M. students? N° 61014 Horacio Zevallos Gámez in Iquitos in 2023? regarding the research design, it is defined as non-experimental, relational, field, and transversal. The population of interest is identified, which is also the sample, 400 students from the educational institution. Data collection instruments, an observation guide and a questionnaire are designed and evaluated and validated by experts. Data collection is carried out through observation and survey of students, and then data analysis is carried out, using statistical tests. The data revealed a Pearson correlation coefficient of 0.629, indicating a moderate to high direct and positive relationship between value attitudes and social skills in the classroom. This relationship is clearly visualized in the scatterplot, where the points follow a positive linear trend. In other words, as value attitudes increase, social skills in the classroom also increase.